N,N-Dimethyl-4-[(2-pyridyl)diazenyl]aniline - Nararak Leesakul; Suthirat Yoopensuk; Chaveng Pakawatchai; Saowanit Saithong; Kanidtha Hansongnern (Acta Crystallographica Section E, 2010)
The title compound, C13H14N4, adopts a trans configuration about the azo bond. There is a dihedral angle of 12.18 (7)° between the pyridine and benzene rings and the mean plane of the dimethylamino substituent is twisted by 6.1 (2)° relative to the benzene ring. In the crystal, weak intermolecular C—H...N hydrogen bonds result in a zigzag arrangement along [010].